Measuring Reflective Inquiry in Professional Learning Networks: A Conceptual Framework - Ariadne Warmoes; Chris Brown; Iris Decabooter; Els Consuegra (Education Sciences)
This study introduces a conceptual framework to measure reflective inquiry in professional learning networks (PLNs). The framework represents a continuum of three components: critical dialog, the use of multiple data sources, and depth of reflection. It is validated through 8 h of PLN conversations (2195 contributions). The results show that the majority of dialog within PLNs consisted of free-flowing discussions (64.37%), using personal experiences as data source (92.57%), and descriptive reflection with external attribution (R1: 79.82%). High-level reflective inquiry was rare (0.18%). Findings highlight the need for skilled facilitation and strategies to foster reflective inquiry.